Coping with difficult situations in the context of the teacher's managerial competences (R&E-SOURCE, 2025)
In this article, we deal with the issue of managing stressful situations in working life in the context of the teacher's managerial competencies. We draw attention to the importance of stress management strategies and challenging situations teachers have to face in their daily work. The teaching profession places significant demands on the teacher's personality, which also plays an important role in managing the workload. It is currently necessary to find out the overall level of stress and the ways in which teachers manage stressful situations. Knowledge of load management principles can be beneficial for everyone. They have the potential to significantly facilitate coping with challenging work and life situations.  The more we learn about ways to handle difficult situations, the more we learn about the impact of stress and its effective management in the work environment.